REMITTANCE & DEVELOPMENT: A SENSITIVITY ANALYSIS OF BANGLADESH - Sajjad Hossain, B M; Noor, Mohammad Ashif; Hossain, Md. Toufique (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
Remittances enhance savings and investment and thus help augment capital formation and overall economic development. There is a definite correlation between macro-economic policies operational in the remittance-receiving state and its flow. Here the hypothesis testing of this study indicates that the sensitivity of the GNP or available foreign reserve total to the yearly remittance flow volatile in the case of Bangladesh. Yearly flow of remittance and GNP in Bangladesh are not independent. Very limited empirical works had been done in relation to the actual impact of remittances on incomes. This paper has used to explore the actual impacts of remittance on GNP through scientific analysis. As inflation and exchange rates affect the flow of remittance so it is an important consideration for migrants with the ability and proclivity to save. However, the paper tries to summarize the empirical verification as well as the results and potentiality of such flows of remittance on GNP and the economic growth of Bangladesh.